STUDY OF IDEAS ABOUT RESPONSIBLE FATHERHOOD IN YOUNG PEOPLE WHO DO NOT HAVE THEIR OWN CHILDREN - S. N. Savinkov; V. V. Kozyreva (Вестник университета)
The problem of studying the ideas of responsible fatherhood in young people aged 18 to 25 years, who do not have their own children has been considered. An empirical study of the existing attitudes towards responsible paternity in young people at this age has been presented. Fatherhood as a dynamic, socio-cultural phenomenon, which has a clear image in every culture, as well as fixed in national traditions and ideas, has been revealed. A projective technique “Unfinished sentences” has been carried out to identify unconscious attitudes to fatherhood, reveal constructive and non-constructive components of these concepts. The aim of the study is to identify ideas about responsible fatherhood in young people in this age group.